Prevalence and Identification of Digestive Tract Protozoa in Goats in Labang District Bangkalan Regency - Warda Nafalizza Efendi; Lucia Tri Suwanti; Abdul Samik; Poedji Hastutiek; Mufasirin Mufasirin; Kusnoto Kusnoto (Journal of Parasite Science (JoPS), 2019)
This study aims to determine the prevalence and to identify gastrointestinal protozoa in goats in Sub-district of Labang, Bangkalan Regency, Madura, Indonesia. The research was conducted in April - July 2019 with 100 samples of goat’s stool. Examination was done in the laboratory of Parasitology in Faculty of Veterinary Medicine, Airlangga University using direct smear, sedimentation and flotation methods. The result showed that goats in Labang, Bangkalan Regency were infected by protozoa Eimeria sp. and Blastocystis sp. and the prevalence was 84%. There were no significant differences in the age and sex of goats (p > 0.05).